With climate change impacts accelerating, we need to re-think the human right to water - Mehta, Lyla; Ringler, Claudia; Varghese, Shiney (Institute of Development Studies, 2020)
This year’s theme for World Water Day is Water and Climate Change. The recent Australian drought and flooding in the UK and East Africa show how climate change is leading to extreme events that create both uncertainties and irregularities in water availability, with far-reaching impacts on human wellbeing and ecosystem health. In all cases, the poor and marginalised people are most at risk. The impact of the COVID-19 pandemic on the global economy will further heighten the existing vulnerabilities of the poor.